A rhetoric of ruins exploring landscapes of abandoned modernity - Wood, Andrew F. (Lexington studies in contemporary rhetoric., 2021)
"A Rhetoric of Ruins combines conceptual and theoretical frameworks to explore ghost towns, disaster sites, and environmental badlands as remnants of modernity. Methods of analysis include Jeremiadic, hauntological, psychogeographic, and heterotopian ways of reading U.S. and international sites"--